Selected Decisions (9th Ed). (Selected Decisions; Issue, Year, 1981)
This paper presents Selected Decisions and Selected Documents' Ninth Issue of the IMF. This volume, the Ninth Issue of Selected Decisions of the IMF and Selected Documents, contains the decisions, interpretations, and resolutions of the Executive Board and the Board of Governors of the IMF to which frequent reference is made in the current activities of the IMF. In addition, the volume contains certain documents relating to the IMF and the United Nations. This issue includes those decisions published in the Eighth Issue and in the Supplement to that issue that remain in effect, as well as new decisions adopted after the publication of the Supplement. The procedures set forth in Section IV of SM/77/277 are approved, and members shall be guided by the considerations in Section IV with respect to the prompt notification of any changes in their exchange arrangements. Once the procedures for initial notification have been clarified, only a few issues remain to be dealt with in respect of subsequent notifications.